2014
DOI: 10.1097/acm.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Medical Student Mistreatment and Its Association With Burnout

Abstract: Purpose Medical student mistreatment has been recognized for decades and is known to adversely impact students both personally and professionally. Similarly, burnout has been shown to negatively impact students. This study assesses the prevalence of student mistreatment across multiple medical schools and characterizes the association between mistreatment and burnout. Method In 2011, the authors surveyed a nationally representative sample of third-year medical students. Students reported the frequency of mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
242
1
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(276 citation statements)
references
References 42 publications
11
242
1
9
Order By: Relevance
“…It should be noted that this is an opportune time to bring this discussion to the forefront in this country, because the new national curriculum guidelines that were recently approved state that medical schools should be able to provide training for doctors to practice "general, humanistic, critical, reflective and ethical medicine (…) with social responsibility and commitment to the defense of citizenship [and] human dignity". 37 Considering the negative impact of mistreatment on mental health and wellbeing, and the way in which students perceive their course and academic achievements, 5,7,12,[16][17][18][19][20] occurrences of mistreatment during medical training have high potential to compromise quality of care and the way in which students approach their patients and their suffering. Mistreatment represents an additional source of stress for medical students that should be seriously taken into consideration by medical schools.…”
Section: Consequences Of Mistreatment On the Way Students Perceive Mementioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that this is an opportune time to bring this discussion to the forefront in this country, because the new national curriculum guidelines that were recently approved state that medical schools should be able to provide training for doctors to practice "general, humanistic, critical, reflective and ethical medicine (…) with social responsibility and commitment to the defense of citizenship [and] human dignity". 37 Considering the negative impact of mistreatment on mental health and wellbeing, and the way in which students perceive their course and academic achievements, 5,7,12,[16][17][18][19][20] occurrences of mistreatment during medical training have high potential to compromise quality of care and the way in which students approach their patients and their suffering. Mistreatment represents an additional source of stress for medical students that should be seriously taken into consideration by medical schools.…”
Section: Consequences Of Mistreatment On the Way Students Perceive Mementioning
confidence: 99%
“…Those who are exposed feel more stressed and depressed, have low self-esteem and are more likely to consume alcohol and binge-drink. 5,7,12,[17][18][19] The different sources of stress to which medical students are exposed during their medical training are well known. 18,26,27 Medical education is hard to access and difficult to sustain, given the large amount of time dedicated to academic activities and the amount of suffering and distress that students need to cope with on a daily basis.…”
Section: Consequences Of Mistreatment On the Way Students Perceive Mementioning
confidence: 99%
See 1 more Smart Citation
“…Some students might experience anxiety related to even working, speaking, or listening to an attending physician like Dr. Charles, and their educational experience could suffer as a result. For example, a national survey of third-year medical students conducted in 2011 found that the majority of respondents reported at least one incident of mistreatment by faculty or residents since they began their clinical rotations [9]. A smaller subset of students also reported recurrent mistreatment by faculty or residents, and these students were more likely to have higher burnout than students who reported no or infrequent mistreatment [9].…”
Section: Loss Of Identitymentioning
confidence: 99%
“…For example, a national survey of third-year medical students conducted in 2011 found that the majority of respondents reported at least one incident of mistreatment by faculty or residents since they began their clinical rotations [9]. A smaller subset of students also reported recurrent mistreatment by faculty or residents, and these students were more likely to have higher burnout than students who reported no or infrequent mistreatment [9]. Although the survey did not define or give examples of "mistreatment," mistreatment could be defined in a variety of ways, including racial or gender discrimination, physical intimidation, or humiliation or belittlement (as in the case presented in figure 1).…”
Section: Loss Of Identitymentioning
confidence: 99%